A rubber sealing material and preparation method thereof

By using nitrile rubber, polyvinyl chloride resin and modified carbon nanotubes in the sealing materials, the existing sealing materials are solved in the lack of toughness and elasticity when improving friction and sealing performance, and the preparation of high-performance sealing materials is realized, with excellent wear resistance and flame retardant properties.

CN116478461BActive Publication Date: 2025-04-15马鞍山海鹰新材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310413129.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-04-15
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

While improving friction and sealing properties, existing sealing materials are difficult to maintain the toughness and elasticity of the rubber matrix, and the uniform dispersion of inorganic fillers is difficult to affect the mechanical properties, and the rubber is flammable, limiting its application.

Method used

Nitrile rubber and polyvinyl chloride resin are used as substrates, combined with modified carbon nanotubes, and rubber sealing materials are prepared through plasticizing, heat refining and vulcanization processes to improve the friction, sealing and wear resistance of the materials and impart flame retardant properties.

Benefits of technology

It realizes the high toughness, elasticity, wear resistance and flame retardant properties of rubber sealing materials, and improves the service life and scope of application of seals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004183915330000031
    Figure BDA0004183915330000031
  • Figure BDA0004183915330000032
    Figure BDA0004183915330000032
  • Figure BDA0004183915330000041
    Figure BDA0004183915330000041
Patent Text Reader

Abstract

The invention discloses a rubber sealing material and a preparation method thereof, which belongs to the technical field of sealing materials, and comprises the following raw materials by weight: 70 parts of nitrile rubber, 25-35 parts of polyvinyl chloride resin, 3-4 parts of antioxidant, 15-20 parts of modified carbon nanotubes, and 2-3 parts of sulfur; the raw materials are mixed, plasticized, vulcanized and the like in proportion to obtain the sealing material. The sealing material of the present invention adopts nitrile rubber and polyvinyl chloride resin as a matrix, and has high toughness, elasticity, friction resistance and sealing performance; by adding modified single-walled carbon nanotubes, it can not only promote the uniform dispersion of single-walled carbon nanotubes in the material, better play a reinforcing role, but also promote the formation of a stable network structure, so that the sealing material has excellent wear resistance, and in addition, it can also give the sealing material efficient, stable and lasting flame retardant performance, thereby improving the scope of application of the sealing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sealing materials, and in particular, relates to a rubber sealing material and a preparation method thereof. Background Art

[0002] For motion seals, friction is an important factor related to the quality of motion. Seals and friction always restrict each other. Generally speaking, improving sealing will increase friction, which directly leads to a decrease in motion capacity and quality; and friction will accelerate the wear of seals.

[0003] At present, most of the common seals are made of EPDM or nitrile rubber, etc. However, as a kind of seal material, its friction performance still needs to be further improved; compared with rubber, plastic generally has a lower friction coefficient, better barrier properties, and higher strength and hardness. During the friction process, due to the higher hardness of plastic, the abrasive wear of plastic is smaller. In order to improve the sealing performance of rubber seals, it is proposed to combine the advantages of high-performance special plastics and rubber, while ensuring that the toughness and elasticity of the rubber matrix are not weakened, and greatly improve the friction and sealing performance of rubber.

[0004] However, the above-mentioned improvement on the wear resistance and mechanical properties of the sealing material is limited. Therefore, some existing technologies will use reinforcing fillers to further improve the performance of the sealing material. However, general reinforcing fillers are inorganic fillers, which are difficult to disperse evenly, which not only reduces the reinforcement effect, but also has a negative impact on the mechanical properties of the material. In addition, since rubber is composed of C and H elements, its oxygen index is low and it is easy to ignite in the air. After ignition, the small molecules decomposed can react with oxygen to generate a large amount of heat, further intensifying the combustion. It cannot self-extinguish in the air, which limits its application in sealing materials in limited spaces. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a rubber sealing material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A rubber sealing material, comprising the following raw materials, measured by weight: 70 parts of nitrile rubber, 25-35 parts of polyvinyl chloride resin, 3-4 parts of antioxidant, 15-20 parts of modified carbon nanotubes, and 2-3 parts of sulfur;

[0008] The preparation method of the rubber sealing material comprises the following steps:

[0009] The first step is to add nitrile rubber and polyvinyl chloride resin into an internal mixer and plasticize for 3-4 minutes, then add an antioxidant and mix for 2-4 minutes, then add the modified carbon nanotubes and mix for 3-5 minutes, and then stand for 50-60 minutes to obtain a mixed material;

[0010] The second step is to add the mixed material into the open mill and heat it at 40-60℃ for 2-4 minutes, add sulfur, and after the powder is eaten up, adjust the roller distance to 1-2mm, make triangle packs 5-6 times, release the roller distance to get the rubber material;

[0011] The third step is to refine the rubber material through an open mixing mill, and then go through a preforming and vulcanization molding process to obtain a rubber sealing material.

[0012] Furthermore, the antioxidant is any one of antioxidant RD, antioxidant 4010NA and antioxidant 445.

[0013] Furthermore, the modified carbon nanotubes are prepared by the following steps:

[0014] S1, react 9-decene-1-ol with sodium hydroxide to obtain 9-decene-1-alcohol sodium for standby use; pass N 2 The air in the four-necked flask is removed, hexachlorocyclotriphosphazene is dissolved in tetrahydrofuran and the flask is placed in an ice bath, and then a tetrahydrofuran mixed solution containing sodium 9-decene-1-olate and triethylamine is slowly and uniformly added dropwise under stirring (the dropping speed is controlled at 2 mL / min), and after the dropwise addition is completed, the mixture is reacted in an ice-water bath for 4 hours. After the reaction is completed, the generated salt (NaCl) is removed by suction filtration, and the filtrate is collected. The solvent and excess triethylamine are removed by vacuum distillation, and then the mixture is washed several times with chloroform and distilled water respectively, and the organic layer is taken, rotary evaporated, and vacuum dried to obtain a phosphazene derivative; the ratio of hexachlorocyclotriphosphazene, sodium 9-decene-1-olate and triethylamine is 0.03 mol:0.09 mol:0.1 mol;

[0015] The -Cl group on the hexachlorocyclotriphosphazene molecule undergoes a nucleophilic substitution reaction with 9-decen-1-ol. By controlling the molar ratio of the two to 1:3, a tri-substitution reaction occurs under the effect of steric hindrance. The process is as follows:

[0016]

[0017] S2. In a three-necked flask, p-aminophenylethylamine was dissolved in methanol, and triethylamine was added as a catalyst. Then, tert-butyloxycarbonyl anhydride was dissolved in ether, and the mixture was dripped into the three-necked flask dropwise from a constant pressure funnel. The mixture was stirred and reacted at a constant temperature of 3-5°C for 10 hours. Water and ether were added, and the mixture was extracted. The ether phase was taken and the ether was removed by rotary evaporation. Finally, the mixture was recrystallized and purified with a mixed solution of dichloromethane and ether (the volume ratio of dichloromethane to ether was 1:1) to obtain a grafting agent. The ratio of p-aminophenylethylamine, triethylamine and tert-butyloxycarbonyl anhydride was 0.1 mol:0.11 mol:0.1 mol.

[0018] Through tert-butyloxycarbonyl anhydride and -NH 2 The reaction of -NH 2 Protected by tert-butyl (Boc) to obtain a grafting agent;

[0019]

[0020] S3, dichloromethane is added to a four-necked flask, nitrogen is introduced, and after continuing for 10min (removing the air in the flask), a phosphazene derivative and triethylamine are added, and stirring and mixing are uniform, and then a dichloromethane solution dissolved with a grafting agent is dripped dropwise using a constant pressure funnel. After the dropwise addition is completed, the reaction is carried out at room temperature for 4h. After the reaction is completed, the generated triethylamine hydrochloride is removed by suction filtration, and the filtrate is distilled under reduced pressure to obtain a primary product; the ratio of the amount of the phosphazene derivative, triethylamine and grafting agent is 35.3g:15.3g:35.4g;

[0021] The -Cl on the phosphazene derivative molecule and the -NH on the grafting agent molecule 2 A nucleophilic substitution reaction occurs to obtain the initial product. The reaction process is as follows:

[0022]

[0023] S4, the initial product was mixed with a saturated solution of THF (tetrahydrofuran) in hydrogen chloride at a solid-liquid ratio of 1 g: 8 mL, stirred at room temperature for 5 h, filtered, the filter cake was rinsed with ether, and vacuum dried to obtain a modifier;

[0024] The initial product was deprotected under acidic conditions to obtain -NH 2 , to obtain a modifier with the structure shown below:

[0025]

[0026] S5, the carboxylated carbon nanotubes were mixed with anhydrous dichloromethane and then ultrasonically dispersed for 30 minutes, HATU (2-(7-azabenzotriazole)-tetramethyluronium hexafluorophosphate) and DIPEA (N,N-diisopropylethylamine) were added, and the ultrasonication was continued for 20 minutes, and then the modifier was added, stirred for reaction for 12 hours, and finally centrifuged, washed, and dried to obtain modified carbon nanotubes; the ratio of the amount of carboxylated carbon nanotubes, HATU, DIPEA, and modifier was 1g:2.8g:2.2mL:8.9g;

[0027] Under the action of HATU and DIPEA, -COOH on the surface of carboxylated carbon nanotubes and -NH 2 An amidation reaction occurs, and the molecular chains of the modifier are chemically bonded to the surface of the carbon nanotube to obtain modified carbon nanotubes.

[0028] After the single-walled carbon nanotubes are modified, an organic molecular layer is formed on the surface, which can effectively improve the interfacial compatibility between the single-walled carbon nanotubes and the polymer matrix (nitrile rubber, polyvinyl chloride); in addition, the grafted modifier molecular chain contains a long aliphatic carbon chain, and the end of the aliphatic carbon chain is an unsaturated carbon-carbon double bond. The long aliphatic carbon chain has a very high similarity and compatibility with the main molecular chain of the polymer matrix, and because of its high flexibility, it can freely penetrate between the polymer chains. Therefore, it can further improve the uniform dispersion of carbon nanotubes in the material, better play a reinforcing role, and thus improve the wear resistance of the material. When the single-walled carbon nanotubes are oriented at 90° in the composite system, their extremely strong adsorption performance The strong van der Waals force on the surface will adsorb a large amount of NBR and PVC molecular chains, making the material matrix very stable, and less surface material will fall off during friction, thereby improving the wear resistance of the material; in addition, the unsaturated carbon-carbon double bonds at the ends can participate in the melt polymerization process of NBR and PVC, and multiple unsaturated carbon-carbon double bonds can play a cross-linking role, which can not only improve the interaction between NBR and PVC, but also promote the formation of a stable network structure, so that the binding force between the internal molecular chains of the sealing material is increased, and the relative sliding between the molecular chains is reduced, so that the sealing material has excellent wear resistance and increases the service life of the seal made of the sealing material;

[0029] It should be further explained that the grafted modifier molecules contain cyclophosphazene groups, which are PN synergistic flame retardant components. As the carbon nanotubes are evenly distributed in the sealing material, they can not only give the sealing material good flame retardant properties, but also have a long-lasting and stable flame retardant effect due to the strong interaction with the material matrix, thereby improving the application scope of the sealing material.

[0030] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps:

[0031] The single-walled carbon nanotubes were placed in a conical flask, and then a strong acid (98% by mass concentrated sulfuric acid and 37.5% by mass concentrated hydrochloric acid mixed in a volume ratio of 5:1) was added according to a solid-liquid ratio of 1g:12mL, and ultrasonic treatment was performed in a 50°C water bath for 6h. After the mixture was cooled to room temperature, deionized water was added to dilute it, centrifuged, and washed with ethanol and deionized water for 3 times in sequence, and finally dried in a 60°C vacuum oven to constant weight, and ground through a 200-mesh sieve to obtain carboxylated carbon nanotubes.

[0032] The single-walled carbon nanotubes are oxidized by strong acid to introduce -COOH functional groups on the surface of the carbon nanotubes, laying the foundation for reaction sites for subsequent modification.

[0033] Further, in step S1, the specific process of the reaction of 9-decen-1-ol and sodium hydroxide is:

[0034] In a four-necked flask equipped with a thermometer, a distillation column and a water separator, 20 g (0.5 mol) of solid sodium hydroxide and 207.4 g (1.4 mol) of 9-decene-1-ol were added in sequence, and the temperature was raised to reflux temperature with magnetic stirring under nitrogen protection. The water produced by azeotropy was collected by a water separator until no obvious water droplets fell in the water separator, and the reaction was completed to obtain sodium 9-decene-1-ol; the molar ratio of sodium hydroxide to 9-decene-1-ol was 1:1.

[0035] Beneficial effects of the present invention:

[0036] The sealing material of the present invention adopts nitrile rubber and polyvinyl chloride resin as a matrix, and can combine the advantages of the two to form a rubber-plastic composite material with high toughness, elasticity, friction resistance and sealing performance; by adding modified single-walled carbon nanotubes, it can not only promote the uniform dispersion of the single-walled carbon nanotubes in the material and better play a reinforcing role, but also promote the formation of a stable network structure, so that the binding force between the internal molecular chains of the sealing material is increased, and the relative sliding between the molecular chains is reduced, so that the sealing material has excellent wear resistance. In addition, it can also give the sealing material efficient, stable and long-lasting flame retardant performance, thereby improving the application range of the sealing material. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] Preparation of carboxylated carbon nanotubes:

[0040] 10 g of carbon nanotubes were placed in a conical flask, and then 120 mL of strong acid (100 mL of 98% by mass concentrated sulfuric acid and 20 mL of 37.5% by mass concentrated hydrochloric acid) was added, and ultrasonic treatment was carried out in a 50°C water bath for 6 h. After the mixture was cooled to room temperature, 300 mL of deionized water was added to dilute it, centrifuged, and washed with ethanol and deionized water for 3 times in sequence. Finally, it was dried in a vacuum oven at 60°C to constant weight, and ground through a 200-mesh sieve to obtain carboxylated carbon nanotubes.

[0041] Example 2

[0042] Preparation of sodium 9-decene-1-olate:

[0043] Into a four-necked flask equipped with a thermometer, a distillation column and a water separator, 8 g of solid sodium hydroxide and 31.2 g of 9-decene-1-ol were added in sequence, and the temperature was raised to reflux temperature with magnetic stirring under nitrogen protection. The water produced by azeotropy was collected with a water separator until no obvious water droplets fell in the water separator. The reaction was terminated to obtain sodium 9-decene-1-ol.

[0044] Example 3

[0045] Preparation of modified carbon nanotubes:

[0046] S1, pass N 2 The air in the four-necked flask was removed, 10.4 g of hexachlorocyclotriphosphazene was dissolved in 100 mL of tetrahydrofuran, and the flask was placed in an ice bath. Then, 40 mL of a tetrahydrofuran mixed solution containing 16 g of sodium 9-decene-1-ol (prepared in Example 2) and 10.1 g of triethylamine was slowly and uniformly added dropwise under stirring for 20 minutes. After the addition was completed, the mixture was reacted in an ice-water bath for 4 hours. After the reaction was completed, the generated salt (NaCl) was removed by suction filtration, the filtrate was collected, the solvent and excess triethylamine were removed by reduced pressure distillation, and then the mixture was washed several times with chloroform and distilled water, respectively. The organic layer was taken, rotary evaporated, and vacuum dried to obtain a phosphazene derivative;

[0047] S2. In a three-necked flask, 13.7 g of p-aminophenylethylamine was dissolved in 80 mL of methanol, and 11.1 g of triethylamine was added as a catalyst. Then 19.4 g of tert-butyloxycarbonyl anhydride was dissolved in 50 mL of ether, and the mixture was dripped into the three-necked flask dropwise from a constant pressure funnel. The mixture was stirred and reacted at a constant temperature of 3° C. for 10 h. Water and ether were added, and the mixture was extracted. The ether phase was taken and the ether was removed by rotary evaporation. Finally, the mixture was recrystallized and purified with a mixture of dichloromethane and ether (the volume ratio of dichloromethane to ether was 1:1) to obtain a grafting agent.

[0048] S3, 150mL of dichloromethane was added to a four-necked flask, nitrogen was introduced, and after continuing for 10min (removing the air in the flask), 35.3g of phosphazene derivative and 15.3g of triethylamine were added, and the mixture was stirred and evenly mixed, and then 60mL of dichloromethane solution dissolved with 35.4g of grafting agent was dripped dropwise using a constant pressure funnel. After the addition was completed, the reaction was carried out at room temperature for 4h. After the reaction was completed, the generated triethylamine hydrochloride was removed by suction filtration, and the filtrate was distilled under reduced pressure to obtain the initial product;

[0049] S4, 60 g of the initial product was mixed with 480 mL of a saturated solution of THF (tetrahydrofuran) in hydrogen chloride, stirred at room temperature for 5 h, filtered, the filter cake was rinsed with ether, and vacuum dried to obtain a modifier;

[0050] S5. Mix 5 g of carboxylated carbon nanotubes (prepared in Example 1) with 200 mL of anhydrous dichloromethane and disperse them by ultrasonication for 30 min. Add 14 g of HATU and 11 mL of DIPEA, continue ultrasonication for 20 min, then add 44.5 g of modifier, stir and react for 12 h, finally centrifuge, wash with ethanol and deionized water 4 times in sequence, and dry to obtain modified carbon nanotubes.

[0051] Example 4

[0052] Preparation of modified carbon nanotubes:

[0053] S1, pass N 2 The air in the four-necked flask was removed, 20.8 g of hexachlorocyclotriphosphazene was dissolved in 200 mL of tetrahydrofuran, and the flask was placed in an ice bath. Then, 80 mL of a tetrahydrofuran mixed solution containing 32 g of sodium 9-decene-1-ol (prepared in Example 2) and 20.2 g of triethylamine was slowly and uniformly added dropwise under stirring for 40 minutes. After the addition was completed, the mixture was reacted in an ice-water bath for 4 hours. After the reaction was completed, the generated salt (NaCl) was removed by suction filtration, the filtrate was collected, the solvent and excess triethylamine were removed by reduced pressure distillation, and then the mixture was washed several times with chloroform and distilled water, respectively. The organic layer was taken, rotary evaporated, and vacuum dried to obtain a phosphazene derivative;

[0054] S2. In a three-necked flask, 27.4 g of p-aminophenylethylamine was dissolved in 160 mL of methanol, and 22.2 g of triethylamine was added as a catalyst. Then 38.8 g of tert-butyloxycarbonyl anhydride was dissolved in 100 mL of ether, and the mixture was dripped into the three-necked flask dropwise from a constant pressure funnel. The mixture was stirred and reacted at a constant temperature of 5° C. for 10 h. Water and ether were added for extraction. The ether phase was taken and the ether was removed by rotary evaporation. Finally, the mixture was recrystallized and purified with a mixture of dichloromethane and ether (the volume ratio of dichloromethane to ether was 1:1) to obtain a grafting agent.

[0055] S3, 300mL of dichloromethane was added to a four-necked flask, nitrogen was introduced, and after continuing for 10min (removing the air in the flask), 70.6g of phosphazene derivative and 30.6g of triethylamine were added, and the mixture was stirred and evenly mixed, and then 120mL of dichloromethane solution dissolved with 70.8g of grafting agent was dripped dropwise using a constant pressure funnel. After the addition was completed, the reaction was carried out at room temperature for 4h. After the reaction was completed, the generated triethylamine hydrochloride was removed by suction filtration, and the filtrate was distilled under reduced pressure to obtain the initial product;

[0056] S4, 120g of the initial product was mixed with 960mL of a saturated solution of THF (tetrahydrofuran) in hydrogen chloride, stirred at room temperature for 5h, filtered, the filter cake was rinsed with ether, and vacuum dried to obtain a modifier;

[0057] S5. Mix 10 g of carboxylated carbon nanotubes (prepared in Example 1) with 400 mL of anhydrous dichloromethane and disperse them by ultrasonication for 30 min. Add 28 g of HATU and 22 mL of DIPEA and continue ultrasonication for 20 min. Then add 89 g of modifier and stir to react for 12 h. Finally, centrifuge, wash with ethanol and deionized water 4 times in sequence, and dry to obtain modified carbon nanotubes.

[0058] Example 5

[0059] Preparation of rubber sealing materials:

[0060] The first step is to add 700g of nitrile rubber and 250g of polyvinyl chloride resin into an internal mixer and plasticize for 3min, then add 30g of antioxidant RD and mix for 2min, then add 150g of modified carbon nanotubes obtained in Example 3 and mix for 3min, and then stand for 50min to obtain a mixed material;

[0061] The second step is to add the mixed material into the open mill and heat it at 40℃ for 2 minutes, add 20g of sulfur, and after the powder is eaten up, adjust the roller distance to 1mm, make triangle packs 5 times, release the roller distance to get the rubber material;

[0062] The third step is to refine the rubber material through an open mixing mill, and then go through a preforming and vulcanization molding process to obtain a rubber sealing material.

[0063] Example 6

[0064] Preparation of rubber sealing materials:

[0065] The first step is to add 700g of nitrile rubber and 300g of polyvinyl chloride resin into an internal mixer and plasticize for 3.5min, then add 35g of antioxidant 4010NA and mix for 3min, then add 175g of modified carbon nanotubes obtained in Example 4 and mix for 4min, and then stand for 55min to obtain a mixed material;

[0066] The second step is to add the mixed material into the open mill and heat it at 50℃ for 3 minutes, add 25g of sulfur, and after the powder is eaten up, adjust the roller distance to 2mm, make triangle packs 6 times, release the roller distance to get the rubber material;

[0067] The third step is to refine the rubber material through an open mixing mill, and then go through a preforming and vulcanization molding process to obtain a rubber sealing material.

[0068] Example 7

[0069] Preparation of rubber sealing materials:

[0070] The first step is to add 700g of nitrile rubber and 350g of polyvinyl chloride resin into an internal mixer and plasticize for 4min, then add 40g of antioxidant 445 and mix for 4min, then add 200g of modified carbon nanotubes obtained in Example 3 and mix for 5min, and then stand for 60min to obtain a mixed material;

[0071] The second step is to add the mixed material into the open mill and heat it at 60℃ for 4 minutes, add 30g of sulfur, and after the powder is eaten up, adjust the roller distance to 2mm, make triangle packs 6 times, release the roller distance to get the rubber material;

[0072] The third step is to refine the rubber material through an open mixing mill, and then go through a preforming and vulcanization molding process to obtain a rubber sealing material.

[0073] Comparative Example

[0074] The modified carbon nanotube raw material in Example 5 is replaced with ordinary single-walled carbon nanotubes, and the other raw materials and preparation process remain unchanged to obtain a rubber sealing material.

[0075] The rubber sealing materials obtained in Examples 5-7 and the comparative example were cut into test samples and subjected to the following performance tests:

[0076] The tensile properties and hardness were measured according to GB / T 528-2009 and GB / T 531.1-2008 respectively;

[0077] The compression set is determined by the test method in GB / T 7759, under the conditions of 70°C, 24h and 25% compression rate;

[0078] Wear resistance is characterized by Akron abrasion value;

[0079] Test the flame retardancy of materials according to UL-94 standard;

[0080] The measured results are shown in the following table:

[0081]

[0082] It can be seen from the data in the above table that the rubber sealing material obtained by the present invention has high mechanical properties, elasticity and wear resistance, and at the same time, also has excellent flame retardant properties; combined with the data of the comparative example, it can be seen that after modification, the single-walled carbon nanotubes can be evenly distributed in the material, exert a reinforcing effect, thereby improving the mechanical properties, and can promote the formation of a cross-linked network structure, improve wear resistance, and give the material efficient flame retardant properties.

[0083] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A rubber sealing material, comprising the following raw materials, by weight: 70 parts of nitrile rubber, 25-35 parts of polyvinyl chloride resin, 3-4 parts of antioxidant, 15-20 parts of modified carbon nanotubes, and 2-3 parts of sulfur, characterized in that: The modified carbon nanotubes are prepared by the following steps: S1, reacting 9-decene-1-ol with sodium hydroxide to obtain sodium 9-decene-1-olate for standby use; introducing N2 to remove air from a four-necked flask, dissolving hexachlorocyclotriphosphazene in tetrahydrofuran, placing the flask in an ice bath, and then slowly and uniformly adding a tetrahydrofuran mixed solution containing sodium 9-decene-1-olate and triethylamine under stirring, reacting in an ice-water bath for 4 hours after the addition is completed, purifying, and obtaining a phosphazene derivative; S2. In a three-necked flask, p-aminophenylethylamine is dissolved in methanol, and triethylamine is added as a catalyst. Then, tert-butyloxycarbonyl anhydride is dissolved in diethyl ether, and the mixture is dripped into the three-necked flask dropwise from a constant pressure funnel. The mixture is stirred and reacted at a constant temperature of 3-5°C for 10 hours. Water and diethyl ether are added for extraction. The diethyl ether phase is taken and the diethyl ether is removed by rotary evaporation. Finally, the mixture is recrystallized and purified with a mixture of dichloromethane and diethyl ether to obtain a grafting agent. S3, add dichloromethane to a four-necked flask, introduce nitrogen, continue for 10 minutes, add phosphazene derivative and triethylamine, stir and mix evenly, then use a constant pressure funnel to dropwise add a dichloromethane solution containing a grafting agent, after the addition is completed, react at room temperature for 4 hours, after the reaction is completed, remove the generated triethylamine hydrochloride by suction filtration, and obtain the primary product after the filtrate is distilled under reduced pressure; S4, the initial product was mixed with a saturated solution of THF in hydrogen chloride at a solid-liquid ratio of 1 g: 8 mL, stirred at room temperature for 5 h, filtered, the filter cake was rinsed with ether, and vacuum dried to obtain a modifier; S5. The carboxylated carbon nanotubes were mixed with anhydrous dichloromethane and then ultrasonically dispersed for 30 minutes. HATU and DIPEA were added, and ultrasonic dispersion was continued for 20 minutes. The modifier was then added, and the reaction was stirred for 12 hours. Finally, the modified carbon nanotubes were obtained by centrifugation, washing, and drying.

2. A rubber sealing material according to claim 1, characterized in that: The purification process in step S1 is: remove the generated salt by suction filtration, collect the filtrate, remove the solvent and excess triethylamine by vacuum distillation, then wash several times with chloroform and distilled water respectively, take the organic layer, rotary evaporate and vacuum dry to complete the purification process.

3. A rubber sealing material according to claim 1, characterized in that: In step S1, the ratio of hexachlorocyclotriphosphazene, sodium 9-decene-1-ol and triethylamine is 0.03 mol:0.09 mol:0.1 mol.

4. A rubber sealing material according to claim 1, characterized in that: In step S2, the ratio of p-aminophenylethylamine, triethylamine and tert-butyloxycarbonyl anhydride is 0.1 mol: 0.11 mol: 0.1 mol.

5. The rubber sealing material according to claim 1, characterized in that: In step S3, the ratio of the amount of the phosphazene derivative, triethylamine and grafting agent used is 35.3 g:15.3 g:35.4 g.

6. A rubber sealing material according to claim 1, characterized in that: In step S5, the ratio of the amount of carboxylated carbon nanotubes, HATU, DIPEA, and modifier is 1 g:2.8 g:2.2 mL:8.9 g.

7. The method for preparing a rubber sealing material according to claim 1, characterized in that: The following steps are involved: The first step is to add nitrile rubber and polyvinyl chloride resin into an internal mixer and plasticize for 3-4 minutes, then add an antioxidant and mix for 2-4 minutes, then add the modified carbon nanotubes and mix for 3-5 minutes, and then stand for 50-60 minutes to obtain a mixed material; The second step is to add the mixed material into the open mill and heat it at 40-60℃ for 2-4 minutes, add sulfur, and after the powder is eaten up, adjust the roller distance to 1-2mm, make triangle packs 5-6 times, release the roller distance to get the rubber material; The third step is to refine the rubber material through an open mixing mill, and then go through a preforming and vulcanization molding process to obtain a rubber sealing material.

Citation Information

Patent Citations

  • Environment-friendly straw modified polyvinyl chloride greenhouse film and preparation method thereof

    CN107501793A

  • Carbon nanometer tube surface modification method and modified carbon nanometer tube

    CN108545717A